Continuous infusion of glucose with model assessment: measurement of insulin resistance and beta-cell function in man. - Hosker, J; Matthews, DR; Rudenski, A; Burnett, M; Darling, P; Bown, E; Turner, R (Springer-Verlag, 1985)
Continuous infusion of glucose with model assessment (CIGMA) is a new method of assessing glucose tolerance, insulin resistance and beta-cell function. It consists of a continuous glucose infusion 5 mg glucose/kg ideal body weight per min for 60 min, with measurement of plasma glucose and insulin concentrations. These are similar to postprandial levels, change slowly, and depend on the dynamic interaction between the insulin produced and its effect on glucose turnover. The concentrations can be interpreted using a mathematical model of glucose and insulin homeostasis to assess insulin resistance and beta-cell function. In 23 subjects (12 normal and 11 with Type 2 (non-insulin-dependent diabetes) the insulin resistance measured by CIGMA correlated with that measured independently by euglycaemic clamp (Rs = 0.87, p less than 0.0001). With normal insulin resistance defined as 1, the median resistance in normal subjects was 1.35 by CIGMA and 1.39 by clamp, and in diabetic patients 4.0 by CIGMA and 3.96 by clamp. In 21 subjects (10 normal and 11 Type 2 diabetic) the beta-cell function measured by CIGMA correlated with steady-state plasma insulin levels during hyperglycaemic clamp at 10 mmol/l (Rs = 0.64, p less than 0.002). The CIGMA coefficient of variability was 21% for resistance and 19% for beta-cell function. CIGMA is a simple, non-labour-intensive method for assessing insulin resistance and beta-cell function in normal and Type 2 diabetic subjects who do not have glycosuria during the test.